Interdisciplinarity of hydropedology - Kutílek, Miroslav; Nielsen, Donald R. (Geoderma, 2007)
A new interdisciplinary subject hydropedology is developing owing to the necessity of sustaining optimal environments. Hydropedology provides the bridge between the disciplines of pedology, including soil macro- and micromorphology and vadose zone hydrology together with other disciplines dealing with land, air and water interfaces. Soil taxons and soil-forming processes are defined phenomenologically. Soil-forming processes which are usually linked have rates that differ by orders of magnitude. And, if soil polygenesis is considered, too, the equilibrium concept between the properties of soil taxons and soil forming factors is not applicable. The coupling of such processes on various tensorial orders leads to the conclusion that anisotropy is a general characteristic of soils. In order to ascertain the links between pedology and hydropedology, the formulation of physically meaningful transport parameters from a quantified knowledge of soil micromorphology is required. This linkage is achieved when the pore size distribution is reflected by the soil hydraulic functions, i.e. by the soil water retention equation and by the unsaturated hydraulic conductivity function. In future research, parameters of such functions must be related to quantified soil micromorphologic characteristics. The first attempt evaluating both functions is presented for soils manifesting a distinct bi-modal pore size distribution. A close cooperation of hydropedology with soil chemistry and microbiology will produce an insight into the role of organic substances upon the change of soil hydraulic parameters. The substances appear either as a consequence of soil pollution, or due to soil organic matter transformation. An example is presented on the change of saturated hydraulic conductivity caused by the adsorption of organic cations. Similar linkages are expected from the cooperation of hydropedology with plant physiology when the role of plant exudates upon the change of soil hydraulic functions is studied.